A review of the impacts of corvids on bird productivity and abundance. (January 2015) - Madden, Christine F.; Arroyo, Beatriz; Amar, Arjun; Sanchez‐Zapata, Jose A.
<x xml:space="preserve">Abstract</x> Corvids are often viewed as efficient predators capable of limiting prey species populations. Despite this widely held belief, a comprehensive review quantifying the effect of corvids on the demography of prey species is lacking. We examine the impacts of crows, ravens Corvus spp. and Eurasian Magpies Pica pica on the population parameters of other bird species. We summarize results from 42 studies, which included 326 explicit evaluations of relationships between a corvid and a potential prey species. Population parameters of studied prey species were categorized as abundance‐related (numbers, nest density) or productivity‐related (nest success, brood size). Information from both experimental removal studies and correlative studies was examined. Combining all studies, no negative influence of corvids on either abundance or productivity of prey species was found in 81% of cases. Negative impacts were significantly more likely in cases examining productivity rather than abundance (46 vs. 10%). Experimental studies that removed only corvid species were significantly less likely to show a positive impact on productivity than those removing corvids alongside other predators (16 vs. 60%). This suggests that the impact of corvids is smaller than that of other predators, or that compensatory predation occurs. The impact of corvids was similar between diverse avian groups (such as gamebirds, passerines and waders; or ground‐nesting and other species). Crows were found to be significantly more likely to have a negative impact on prey species productivity than were Magpies (62 vs. 12%), but no differences were found in relation to prey abundance. We conclude that while corvids can have a negative impact on bird species, their impact is small overall, and nearly five times more frequent for productivity than for abundance. These results suggest that in most cases bird populations are unlikely to be limited by corvid predation and that conservation measures may generally be better targeted at other limiting factors. However, negative impacts were found in a minority of cases, and those may require further investigation to develop management tools to mitigate such impacts where they are of economic or conservation concern.